Mental health challenges faced by professional athletes - Dawid Szczepanek; Katarzyna Szczurek; Adrianna Biecka; Mikołaj Wyrzykowski (Quality in Sport)
Background: Sport psychiatry is a dynamic and constantly developing discipline of medicine. Professional athletes may experience a variety of mental health problems that influence their everyday life and sport performance. Therefore, the potential risk factors for developing mental disease should be known to coaches and physicians to provide adequate help for athletes.